Violence and prison: an approach to culture within walls from overcrowding in Costa Rica - Ramírez Flores, Stephanie (2022)
This work has been undertaken as part of the academic project UNA pedagogía para el reencuentro: derechos humanos, educación y literatura en centros de atención institucional de Costa Rica of Universidad Nacional de Costa Rica (UNA) and the Instituto de Estudios Latinoamericanos (IDELA). It covers the problem of prison overcrowding in the Costa Rican penal system: due to this issue, a large number of human rights are violated day by day to the extent of becoming a worrying and urgent problem to address. The country has entered a prison crisis where the dignity of people deprived of liberty has been diminishing with ill-treatment in terms of food, recreation, and health. The accumulation of these factors has generated the constitution of a violent prison culture; human interaction between walls is constituted between tensions and indifference among inmates.